“It Puts us in our Students’ Shoes”: Listening to Voices from Teacher Candidates on Their Test-Taking Experience - Cheng, Liying; Ma, Jia (International Journal of Humanities and Social Science Research, 2015)
This study explores teacher candidates’ experiential learning through their test-taking experiences while attending a Bachelor of Education (B. Ed.) program. Eighty-four written reflections by teacher candidates taking a mid-term course examination on classroom assessment practices were analyzed. Major themes emerging from these reflections on the test-taking experience are related to validity concepts of construct representation, construct-irrelevant variance, relevance, and fairness. The study reveals that the test-taking experience could be valuable to teacher candidates in their learning of classroom assessment practices and in their understanding of the issues in test taking that may influence test performance. This, in turn, could potentially provide teacher candidates with a direct framework for their future classroom assessment practices, by which they may support their own future students.